Health Services Planning - Thomas, Richard K. (Springer US, 2003)
Health Services Planning provides the reader with an understanding of the key concepts related to the planning process and offers step-by-step guidelines for developing any type of plan for a community, a health system or an organization. The author addresses the challenge of health planning at both the community level and within the healthcare organization. In addition, the book provides detailed guidance on the development of strategic plans, business plans, and marketing plans. The book provides background on the sociocultural context for health planning and the nature of the demand for health services. Resource material is provided on the research process necessary to support planning activities and sources of data for health planning. Illustrative material is provided through boxes and exhibits throughout the text. An extensive appendix provides examples of various types of plans drawn from the experiences of the author. A glossary provides the reader with definitions of key terms. Readers will gain an appreciation of the importance of planning for the orderly development of health services at the community or organization level. The necessary skills will be learned to allow the reader to formulate plans or, at the least, be able to intelligently discuss the planning process with other health professionals. Health Services Planning is a useful textbook in health administration programs, as well as a resource to health professionals in both public and private sector healthcare organizations who need to have an understanding of the planning process.